Macronutrients comparison of commercial cat foods in malaysia - Mohd Aiman, Hamdan; Muhammad Fitri, Yusof; Hajar Fauzan, Ahmad; Mufafikri, Musa; Najmuddin, Mohd Ramli; Mohd Najib, Razali (ResearchersLinks Ltd, 2024)
There are many cat food products sold in the current retail market. The cat food product industry is rapidly expanding due to the enlargement of middle-class citizens and the increase in spending on pets per capita. However, there is no validation of the actual nutritional value of these products. The present study aimed to determine the dietary nutrient profile of six commercial cat food available in Malaysia with comparison to the actual requirement of cats. The results showed that Grade A cat food product has a significantly higher protein, fat, moisture, and ash content in comparison to Grade B cat food. Meanwhile, Grade B has a significantly higher carbohydrate content as compared to Grade A cat food. The new cat food formulation innovated from this work via utilizing the local raw materials has the highest protein, fibre, and ash contents but is lower in fat, moisture and carbohydrate content in comparison to commercial cat food products. All of the cat food products in Malaysia that were analysed in this work met the Association of American Feed Control Officials (AAFCO) standard. However, not all cat food products are considered a perfect cat food formulation. This information provides insights into the nutrient profile of commercial cat food available in the Malaysian market.